Analysis of Students' Creativity and Learning Interest in the History of the Indonesian National Movement Course - Pujo Sukino; Sahid Hidayat (Civiliza Publishing, Indonesia., 2026)
Learning creativity is one of the important things in a learning process. Because, learning creativity can train students not to depend on others. This research aims to fully and thoroughly describe the creativity and learning interests of students in the Indonesian National Movement History course for the odd semester 2025/2026. The research method used is descriptive with a qualitative approach. The research techniques used are direct communication, indirect communication and documentation. Research Tools, Observation Guides, Interview Guides, and Learning Documents. The results of the research include 1) The creativity of students in rural and urban history courses in general is quite good, as seen from students who have shown a creative attitude. 2) Factors that can affect student learning creativity are the encouragement of the students themselves and the encouragement of the environment which are the most important factors to support student learning creativity, the attitude of lecturers towards their students' creativity. Factors of lecture materials that are in accordance with historical dynamics during the national movement. Then students want to have an opinion or dare to express their opinion in lectures, dare to actively ask questions and tell stories. 3) The interest in learning in the Indonesian national movement history course is quite high because the topic is interesting to study and discuss.